A centrifugation-first approach for recovering high-yield bio-oil with high calorific values in biomass liquefaction: A case study of sewage sludge. (15th February 2020) - Mujahid, Rana; Riaz, Asim; Insyani, Rizki; Kim, Jaehoon
Graphical abstract: Highlights: Centrifuge-first approach was developed for efficient recovery of bio-oil. Bio-oil was produced using hydrothermal liquefaction of sewage sludge. Centrifuge resulted in 17–23 wt% increase in bio-oil yield than conventional method. Yields and properties of bio-oil did not change much with reaction conditions. Bio-oil had low O/C ratio, low acidity, low water content, and high calorific value. Abstract: A new "centrifuge-first" approach was developed to recover a large amount of bio-oil produced during hydrothermal liquefaction (HTL) of dewatered sewage sludge (DWSS). The entire mixture produced from HTL was first centrifuged to separate the water + water-soluble organics (WSOs) phase from the bio-oil (BO) + solid residue phase, and subsequently, bio-oil was separated from solid residue by simple filtering. The HTL of DWSS at an optimum condition of 325 °C and 12–14 MPa for 30 min resulted in a DWSS conversion of 88%. Under this optimum condition, using the centrifuge-first approach, the yield of bio-oil recovered was 64 wt%, a value that was much higher than that of LLE with dichloromethane (47 wt%) or ethyl acetate (41 wt%). The centrifuge-first approach can be applied to recover bio-oil produced at a variety of HTL parameters, including temperature (300–400 °C), time (30–120 min), and pressure (25–36 MPa). The O/C ratios, calorific values of the bio-oils, and average molecular weights were in the range of 0.03–0.05, 33–36 MJ kg −1, and 130–190 g mol −1, respectively, demonstrating that they were not very sensitive to the process parameters. In addition to the high energy content, the low water content (<1 wt%), low inorganic content (<1 wt%), and low acidity (total acid number <26 mg KOH per g oil) in the bio-oil recovered from the centrifuge-first approach make its use in combustion fuel applications suitable. The major composition of the bio-oils was aromatics, N-cyclic species, and long-chain hydrocarbons.